2004
DOI: 10.1080/01485010490474634
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Some Reproductive Parameters and Biochemical Properties of Blood Serum in Rams

Abstract: The objective of the present study was to describe the relationship between some reproductive parameters, hormonal levels, and some biochemical properties of blood serum in rams under the Afyon province conditions. The total protein and globulin were positively (P < 0.01) correlated with sperm motility and sperm concentration in all of rams. Total lipid was negatively (P < 0.05) correlated with sperm motility and concentration in Daglic, and it was positively (P < 0.01) correlated with percentage of abnormal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
0
1
1
Order By: Relevance
“…seasonal fluctuations of glucose concentration in rams were observed (table 2), the highest concentration was recorded in winter and autumn (81.8±3.753 and 68.7±2.381 mg/ml respectively) and significantly (P≤0.05) decreased in spring and summer (34.8±1.652 and 36.4±1.529 mg/ml respectively), similar results were observed by (31) and this rise in glucose level in winter may be related to inhibition of insulin secretion due to the low nutrition because cold stress (32). The findings of the present study showed (Table 1) that the concentration of cholesterol (53.37±2.836 mg/ml) was higher than recorded by (27,33) in Chios, Daglic and Yankasa rams (35.9, 32.6 and 45.04 mg/ml respectively), while it was lower than recorded by (27) in Ouda rams (63.06 mg/ml). This variation may be due to differences in breed (33).…”
Section: Table (1) Total the Scrotal Circumference Body Condition Scsupporting
confidence: 90%
See 1 more Smart Citation
“…seasonal fluctuations of glucose concentration in rams were observed (table 2), the highest concentration was recorded in winter and autumn (81.8±3.753 and 68.7±2.381 mg/ml respectively) and significantly (P≤0.05) decreased in spring and summer (34.8±1.652 and 36.4±1.529 mg/ml respectively), similar results were observed by (31) and this rise in glucose level in winter may be related to inhibition of insulin secretion due to the low nutrition because cold stress (32). The findings of the present study showed (Table 1) that the concentration of cholesterol (53.37±2.836 mg/ml) was higher than recorded by (27,33) in Chios, Daglic and Yankasa rams (35.9, 32.6 and 45.04 mg/ml respectively), while it was lower than recorded by (27) in Ouda rams (63.06 mg/ml). This variation may be due to differences in breed (33).…”
Section: Table (1) Total the Scrotal Circumference Body Condition Scsupporting
confidence: 90%
“…The findings of the present study showed (Table 1) that the concentration of cholesterol (53.37±2.836 mg/ml) was higher than recorded by (27,33) in Chios, Daglic and Yankasa rams (35.9, 32.6 and 45.04 mg/ml respectively), while it was lower than recorded by (27) in Ouda rams (63.06 mg/ml). This variation may be due to differences in breed (33). On the other hand, significant effect of season on the cholesterol concentration in Nuaimei rams was observed in the current study ( Table 2).…”
Section: Table (1) Total the Scrotal Circumference Body Condition Sccontrasting
confidence: 54%
“…Активність аспартатамінотрансферази проявляється у спермі плідників. Встановлено, що величина активності ензиму в еякулятах, поряд з іншими показниками, може служити маркером запліднювальної здатності сперміїв (Nizański et al, 2001;Kozdrowski, & Dubiel, 2004;Gündoğan et al, 2004;Gaczarzewicz et al, 2010). Тому метою роботи було вивчити активність та вміст ізозимів АСТ в еякулятах бугаїв у зв'язку з виживанням сперміїв.…”
unclassified